The Role of Telomeres and Telomerase in Cellular Aging and Disease: Mechanisms, Implications, and Therapeutic Interventions - Christopher, Grace; Goje, Lazarus Joseph (Darul Yasin Al Sys, 2025)
Telomeres, the protective caps at the ends of chromosomes, play a crucial role in maintaining genomic stability. This review explores the structure and function of telomeres, the mechanisms of telomere shortening, and the role of telomerase in counteracting this process. Telomere shortening is a natural consequence of cell division and is associated with cellular aging, senescence, and apoptosis. The review delves into the molecular biology of telomeres, highlighting the significance of the shelterin complex in protecting telomeres from degradation and fusion. It also discusses the genetic and epigenetic factors influencing telomere length, the impact of oxidative stress and inflammation on telomere attrition, and potential interventions to preserve telomere length. The review concludes with recommendations for lifestyle changes and therapeutic strategies to mitigate telomere shortening and promote healthy aging.